Cross Cultural Adaptation and Psychometric Validation of the Assessment of Recovery Capital for Indonesian Rehabilitation - Fitri Isnaini; Mondastri Korib Sudaryo; Bagus Takwin; Besral Besral (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
ntroduction: A comprehensive understanding of recovery capital, the personal and social resources supporting sustained recovery, is essential in addiction rehabilitation. Indonesia lacks a culturally appropriate, psychometrically validated instrument to assess this construct. This study aimed to cross culturally adapt and validate the Assessment of Recovery Capital (ARC) for the Indonesian rehabilitation context. Methods: A sequential exploratory mixed-method design was employed across an 11- adaptation stage The qualitative phase (steps 1–5) included forward translation, synthesis, expert review, back translation, and harmonization. The quantitative phase (steps 6–10) encompasses content validity (CVI), face validity (FVI) construct validity using exploratory factor analysis (EFA), internal consistency, and test retest reliability, followed by final instrument drafting. Results: The ARC instrument was successfully adapted into Bahasa Indonesia. Content validity was excellent (S-CVI/Ave = 0.98 for relevance; 0.95 for clarity), Face validity demonstrated high comprehensibility (S-FVI/Ave = 0.94 for comprehension;0.96 for clarity). Construct validity among 250 rehabilitation clients supported a 10-factor structure explaining 70.64% of total variance. EFA identified 31 items meeting the dominant factor loading criterion (?0.40), presented in the factor table for reporting clarity, all 50 items were retained in the final instrument based on content validity and conceptual equivalence. internal consistency was acceptable to strong (Cronbach’s alpha = 0.655–0.860) and test–retest stability was good (ICC = 0.719–0.803). The final instrument comprises demographic data, 50 ARC items across 10 domains, and one open-ended question on recovery support needs. Confirmatory factor Analysis (CFA) is recommended inFuther studies. Conclusion: The Indonesian ARC demonstrates preliminary validity, reliability, and cultural relevance for assessing recovery capital among individuals in rehabilitation. It has potential utility for monitoring recovery outcomes and informing evidence based addiction recovery practices in Indonesia, although further validation in border setting is warranted.